THE RELATIONSHIP OF SMOKING HABITS AMONG HYPERTENSION EVENTS IN SINDANG BARANG DISTRICT, BOGOR: HUBUNGAN KEBIASAAN MEROKOK DENGAN KEJADIAN HIPERTENSI DI KELURAHAN SINDANG BARANG KOTA BOGOR - Benny Benny M.P Simanjuntak; Sasni Sasni Triana Putri (Wijaya Husada, 2019)
According to the word health organization (WHO) in 2014 Statistical data states that 247% of the population of shoutheast Asia and 23,3% of indonesia aged 18 years and over exverience hypertension. This study aims to determine the relationship of smoking habits with hypertension events in Sindang Barang village of Bogor City. The type of this research is the research that will be carried out is quantitative research with a correlationnal approach and the cross sectional method of population in this study are population with a total of 250 respondents the sampling technique on this research is taking samples non probable and obtained and questionnaire. Based on the results of the bivariate analysis of dani, 250 respondents as many as 89 respondents, the habit of smoking with hypertension was as much as (69,5%) more than Moderate smokingn habits with moderate hypertension as many as 53 respondents (50,5%) and 15 respondents (88,2%) Baed on the statistics of bivariate analysis table statistics obtained p,value 0,000 and a co.05 then pvalue <a, so that HO is rejected heavily. The statistics show there is a relationship between smoking habits and occurrence Hyipertension in in Sindang Barang village of Bogor City The results of this study are expected to be used as reference material by the community to maintain style and lifestyle are healthy and better.